Ettevõtluse arengut mõjutavad tegurid Eestis (Põhja-Sakala valla näitel) - Aavasalu, Tõnu; Raudjärv, Matti (Estonian Discussions on Economic Policy, 2019)
The article covers the study conducted for a graduation paper of the University of Tartu in Estonia, in the academic year 2018/2019, on factors influencing business development based on the case of the North Sakala Rural Municipality located in Central Estonia. Based on extensive sources of literature, the essence and objectives of regional policy, and the impact of regional development policy and the administrative reform on rural business activities are brought out. Also an overview of the impact of the administrative reform on local government as the developer of business environment and on business development is provided. Rural business activities and the factors influencing them are treated separately, based on the case of the North Sakala Rural Municipality. The survey conducted among heads of businesses of the North Sakala Rural Municipality, and the analysis of its results made it possible to draw a lot of conclusions and make suggestions. Proceeding from the results of the quantitative survey conducted among heads of businesses, the respective proposals have also been submitted to the North Sakala Rural Municipality Government.